The Recent Developments in Power Electronics for Renewable Energy Integration - Aminzadeh, Ali; Pilekouhi, Emran; Banizaman, Hamed; Maesoumi, Mohsen; Bahramizadeh, Amir Hossein (International journal of industrial engineering and operational research, 2024)
This article presents a comprehensive overview of the latest advances in power electronics for the seamless integration of renewable energy sources into the existing power grid. With the increasing penetration of renewable energy systems such as solar and wind power into the power grid, the importance of efficient and reliable power electronics solutions has become paramount. The paper discusses various power electronics topologies, control strategies and modulation techniques that enable efficient integration of renewable energy sources with the grid. challenges and opportunities in power electronics for renewable energy integration are analyzed, along with potential future directions in this rapidly developing field. The findings presented in this paper aim to illuminate the current state-of-the-art and pave the way for further advances in power electronics for renewable energy integration.